Neonatal delirium: fact or fiction? A study protocol of a prospective, observational study at the Neonatal Intensive Care Unit (NICU) - Richel Lousberg; Kim AM Tijssen; Husam KZ Salamah; Kelly MP Hauman; Danilo AWD Gavilanes-Jimenez; Jan NM Schieveld; Jacqueline JMH Strik (BMJ Paediatrics Open)
Introduction Delirium is a neuropsychiatric disorder that remains under-recognised and poorly understood in the paediatric population, especially among the very young. In premature neonates, delirium is not yet researched, even though prematurity may also be implicated as a risk factor since younger age, developmental delay and a vulnerable brain are risk factors. However, given the developmental stage of these patients, the assessment of two important Diagnostic and Statistical Manual of Mental Disorders-V (DSM-V) criteria for diagnosing delirium, disturbance in consciousness/attention and cognition, is complicated and/or even impossible. Therefore, the main aim of the study is to screen for delirium in premature infants at the neonatal intensive care unit.Methods and analysis An exploratory observational prospective cohort study will be conducted at the Maastricht University Medical Centre+ during a period of 12 months to explore the epidemiology (patient/clinical characteristics and prevalence) of delirium. All admitted infants are screened for agitation and apathy as the main delirium markers, using the neonatal pain agitation and sedation scale and the Cornell Assessment of Paediatric Delirium.Ethics and dissemination The study protocol and informed consent procedure were submitted to the Medical Ethics Committee (METC) (METC 2023–3709). The METC waived the need for approval. However, although the METC waived the need for approval, informed consent will be collected for consent for publication of the collected data.